The Influence of Digital-Based Training Programs on Employee Competence in All Threeleanor Aesthetic Clinic Branches: Penelitian - Clarissa Siswara (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the effect of digital-based training programs on employee competency in all Threeleanor Aesthetic Clinic Branches. The research approach used is quantitative with survey techniques. Data collection was carried out through questionnaires distributed to Threeleanor Aesthetic Clinic employees and analyzed using SPSS. The results of the study indicate that digital-based training programs have a significant effect on employee competency in all Threeleanor Aesthetic Clinic branches. Then from the results of the study, the digital-based training program has a very strong relationship with employee competency in all Threeleanor Aesthetic Clinic Branches. These findings indicate that digital training designed and implemented by the company directly contributes to improving the capabilities and quality of human resources.